Dark fermentative hydrogen production and transcriptional analysis of genes involved in the unicellular halotolerant cyanobacterium Aphanothece halophytica under nitrogen and potassium deprivation - Chinchusak, Nattanon; Incharoensakdi, Aran; Phunpruch, Saranya (Frontiers in Bioengineering and Biotechnology, 2023)
The unicellular halotolerant cyanobacterium Aphanothece halophytica is known as a potential hydrogen (H2) producer. This study aimed to investigate the enhancement of H2 production under nutrient deprivation. The results showed that nitrogen and potassium deprivation induced dark fermentative H2 production by A. halophytica, while no differences in H2 production were found under sulfur and phosphorus deprivation. In addition, deprivation of nitrogen and potassium resulted in the highest H2 production in A. halophytica due to the stimulation of hydrogenase activity. The effect of adaptation time under nitrogen and potassium deprivation on H2 production was investigated. The results showed that the highest H2 accumulation of 1,261.96 ± 96.99 µmol H2 g dry wt−1 and maximum hydrogenase activity of 179.39 ± 8.18 µmol H2 g dry wt−1 min−1 were obtained from A. halophytica cells adapted in the nitrogen- and potassium-deprived BG11 medium supplemented with Turk Island salt solution (BG110-K) for 48 h. An increase in hydrogenase activity was attributed to the decreased O2 concentration in the system, due to a reduction of photosynthetic O2 evolution rate and a promotion of dark respiration rate. Moreover, nitrogen and potassium deprivation stimulated glycogen accumulation and decreased specific activity of pyruvate kinase. Transcriptional analysis of genes involved in H2 metabolism using RNA-seq confirmed the above results. Several genes involved in glycogen biosynthesis (glgA, glgB, and glgP) were upregulated under both nitrogen and potassium deprivation, but genes regulating enzymes in the glycolytic pathway were downregulated, especially pyk encoding pyruvate kinase. Interestingly, genes involved in the oxidative pentose phosphate pathway (OPP) were upregulated. Thus, OPP became the favored pathway for glycogen catabolism and the generation of reduced nicotinamide adenine dinucleotide phosphate (NADPH), which resulted in an increase in H2 production under dark anaerobic condition in both nitrogen- and potassium-deprived cells.